The scientific community of lusophone analysts of social networks: which is the potential for collective action? - Varanda, Marta Pedro (2016)
The development of a lusophone academic research in the field of SNA (Social Network Analysis) have experienced an important growth in this last decade, fact that we found in the meeting we have participated in Luso-Afro-Brazilian Conferences (in 2010, Salvador, Brazil) and the SUNBELT (realized in 2011 in Riva Del Garda, Italy). Therefore, we also found the fact that, despite the increase important in this research field, a true Scientific Community was not yet established: the participants do not know themselves, neither work together. The challenge we pose in this article is to explain how the interdependence between the lusophone SNA develops, and what the main variables are we can observe in the process that would explain us the absence of Institutionalization of this Scientific Community.